2020
DOI: 10.12820/rbafs.25e0139
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento sedentário em adolescentes brasileiros: uma revisão sistemática

Abstract: Objetivou-se descrever aspectos metodológicos da pesquisa em comportamento sedentário e identificar intervenções para redução do comportamento sedentário em adolescentes brasileiros. A busca de dados foi de outubro de 2014 a abril de 2019. As bases de dados utilizadas foram LILACS, Pubmed, SciELO e Scopus. Foram critérios de inclusão artigos originais publicados em revistas nacionais e internacionais, teses e dissertações completas disponíveis para download, com amostras que incluíssem adolescentes brasileiros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…High school students in the city of João Pessoa, Paraíba showed a 79.5% prevalence of excessive screen time [25]. A review study by Silva et al [26] showed that the majority of the analyzed studies found a prevalence of exposure to SB greater than 50%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High school students in the city of João Pessoa, Paraíba showed a 79.5% prevalence of excessive screen time [25]. A review study by Silva et al [26] showed that the majority of the analyzed studies found a prevalence of exposure to SB greater than 50%.…”
Section: Introductionmentioning
confidence: 99%
“…The study of SB in adolescents is strongly based on observational research, which does not use direct methods (e.g., accelerometer) for its measurement [30]. Furthermore, the need for research evaluating the exposure to portable technologies is a gap to be covered [26]. The possession of these devices is quite high among Brazilian adolescents [31] as well as those from other nationalities [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…These strategies are segmented and promising because they influence the behavioral activities of this population [ 15 , 17 ]. However, recent studies have pointed out the lack of interventions that specifically address the barriers preventing adolescents from engaging in PA [ 18 , 19 ]. Systematizing results on the most effective interventions to minimize these barriers, despite the scarcity of existing intervention studies, is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Vários estudos têm se dedicado ao tema do CS, contemplando diferentes métodos de mensuração, tipos de comportamento avaliados e grupos, como crianças, adolescentes, universitários, adultos e idosos (Castro et al, 2018;Leão, Knuth & Meucci, 2020;Silva Filho et al, 2020). Entretanto, existe uma lacuna quando se fala sobre o comportamento sedentário em profissionais de saúde.…”
Section: Introductionunclassified